DO MULTIPURPOSE COOPERATIVES HAVE ADDRESSED THEIR MEMBER’S AGRICULTURAL OUTPUT MARKETING CHALLENGES OF SMALL HOLDER FARMERS IN ETHIOPIA? - Wakweya, Rusha Begna (Applied Studies in Agribusiness and Commerce, 2024)
Multipurpose cooperatives offer a powerful tool for enhancing the livelihoods of small-scale farmers, particularly in developing economies. By joining forces, these farmers gain greater collective bargaining power, allowing them to negotiate better prices for their crops and increase their incomes. In developed countries as well, farmer cooperatives play a central role in streamlining production and marketing activities for family farms. They act as a crucial bridge between farmers and markets, ensuring smoother exchange and coordination within the agricultural sector. However, despite their significant contributions, multipurpose cooperatives also face challenges that influence them to play a significant role of agricultural product marketing. The aim of this study was to examine the benefits and difficulties associated with members of a multipurpose cooperative participating in the sale of agricultural products in the Kersa district of Jimma Zone, Oromia Regional State, Ethiopia. For this study, four multipurpose cooperatives were chosen using a two-stage sampling technique, resulting in a sample size of 196 cooperative members. Quantitative data was collected through a structured questionnaire from primary sources, while qualitative data was collected through focus groups and key informant interviews. Descriptive statistics such as mean, chi-square, standard deviation, frequency, and percentage were used to analyze the data. The result showed that 66.36% of cooperative members were participants, whereas 33.64% were non-participants. Multipurpose cooperatives are serving as the primary source of agricultural inputs. However, the output marketing activity of the sampled multipurpose co-operatives in the district is not as remarkable. The study suggests that local cooperative agencies should encourage more members to participate in selling their crops through the cooperatives